Neutrophil transit time and localization within the megakaryocyte define morphologically distinct forms of emperipolesis - Huang, Frank Y.; Cunin, Pierre; Radtke, Felix A.; Grieshaber-Bouyer, Ricardo; Nigrovic, Peter A. (bioRxiv beta, 2021)
In emperipolesis, neutrophils transit through megakaryocytes, but it is unknown whether this interaction represents a single type of cell-in-cell interaction or a set of distinct processes. Using an in vitro model of murine emperipolesis, we characterized neutrophils entering megakaryocytes using live-cell spinning disk microscopy and electron microscopy. Approximately half of neutrophils exited the megakaryocyte rapidly, typically in 10 minutes or less, displaying ameboid morphology as they passed through the host cell (fast emperipolesis). The remaining neutrophils assumed a sessile morphology, most remaining within the megakaryocyte for at least 60 minutes (slow emperipolesis). These neutrophils typically localized near the megakaryocyte nucleus. By ultrastructural assessment, all internalized neutrophils remained morphologically intact. Most neutrophils resided within emperisomes, but some could be visualized exiting the emperisome into the cell cytoplasm. Neutrophils in the cytoplasm assumed close contact with the platelet-forming demarcation membrane system or with the perinuclear endoplasmic reticulum, as confirmed by immunofluorescence microscopy. Together, these findings reveal that megakaryocyte emperipolesis reflects at least two processes, fast and slow emperipolesis, each with its own characteristic transit time, morphology, and intracellular localization, suggesting distinct functions. Key Points Neutrophil passage through megakaryocytes, termed emperipolesis, diverges into fast and slow forms that differ in transit time, morphology, and intracellular localization. During emperipolesis, neutrophils can reside in vacuoles (emperisomes) or escape into the cell cytoplasm to assume positions near the megakaryocyte’s demarcation membrane system, endoplasmic reticulum, or nucleus.
Vorveröffentlichung, noch nicht peer reviewed
Gesehen am 07.06.2021